Effect of high fat diet on the toxicokinetics and toxicodynamics of chlorpyrifos following acute exposure in male C57BL/6J mice. Issue 6 (28th February 2022) - Kondakala, Sandeep; Ross, Matthew K.; Chambers, Janice E.; Howell, George E.
Abstract: Chlorpyrifos (CPS) is one of the most widely used organophosphate (OP) insecticides. The acute neurotoxicity of OPs results from the inhibition of acetylcholinesterase (AChE). However, some OPs also inhibit noncholinergic targets including monoacylglycerol lipase (MAGL), fatty acid amide hydrolase (FAAH), and carboxylesterase (CES). Data have shown that highly lipophilic OPs, including CPS, have a persistent toxic effect in obese patients. Therefore, the present study was designed to determine the effect of high fat diet (HFD) induced obesity on the disposition of CPS and its detoxified metabolite 3, 5, 6‐trichloro‐2‐pyridinol (TCP) following acute exposure as well as effects on cholinergic and noncholinergic CPS targets. Male C57BL/6J mice were fed a standard diet (STD) or HFD for 4 weeks, then treated with vehicle or CPS (25 mg/kg) via oral gavage and euthanized postdosing at 0, 3, 6, and 12 h. Following exposure, CPS levels in adipose tissue of HFD fed animals were increased to a greater extent than in STD fed animals, whereas overall hepatic TCP levels were decreased in HFD fed animals. Red blood cell (RBC) AChE and plasma cholinesterase activities were inhibited regardless of diet intake, but inhibition of RBC AChE activity was significantly lower after 3 h in HFD animals. Hepatic CES and FAAH activities were also significantly decreased following CPS exposure regardless of diet. In conclusion, increased time‐integrated CPS levels in adipose tissue indicate CPS may possibly form a depot there and may be retained longer in obese animals than in normal animals.